KESIAPSIAGAAN MASYARAKAT TERHADAP BENCANA BANJIR DI KECAMATAN MEMPAWAH HILIR KABUPATEN MEMPAWAH - Ramadhan, Rizqi; Buwono, Sri; Adlika, Nur Meily (Universitas Tanjungpura, 2023)
This study aims to determine community preparedness for flood disasters in Mempawah Hilir District, Mempawah Regency. The research method used is quantitative research with survey methods. The source of the data for this research is the people of Mempawah Hilir District who were affected by the flood disaster and the data is the result of field observations along with the distribution of questionnaires to flood-affected communities in Mempawah Hilir District and the total sample calculation results are 99 respondents. The results showed that Mempawah Hilir District has an area with a low level of vulnerability of 12,161.33 Ha, a vulnerable category area has an area of 8,138.26 Ha, and an area with a very vulnerable category has an area of 967.70 Ha. Meanwhile, the preparedness of the people of the Mempawah Hilir sub-district is in the unprepared category with an index value of 55. The calculation is obtained by measuring each preparedness parameter. The knowledge parameter having preparedness with a very ready category with an index of 31, the attitude parameter having an unprepared readiness index with an index of 10, the emergency response parameter having an unprepared preparedness with an index of 30, the early warning parameter having an unprepared preparedness with an index of 8, and the mobilization parameter. the resource has unprepared readiness with index 4.